New records of Ceratocampinae (Lepidoptera: Saturniidae) species from the Cerrado of Maranhão, Brazil - Dos Santos, Alberico Alves; da Silva, Carlos Alberto Domingues; Camargo, Roberto da Silva [UNESP]; Wilcken, Carlos Frederico [UNESP]; Pinheiro, Rodrigo Almeida; Lemes, Pedro Guilherme; Zanuncio, José Cola (FapUNIFESP (SciELO), 2023)
Ceratocampinae (Lepidoptera: Saturniidae) is the second most diverse subfamily of Saturniidae with 300 species described in 30 genera from southern Canada to northern Argentina. Species of this subfamily are widely distributed in Southeast Brazil, with many endemics to the Cerrado, and important as indicators of ecosystem quality. Specimens of Ceratocampinae were collected in the Parque Estadual do Mirador, Maranhão state, Brazil. Adeloneivaia acuta (Schaus, 1896), Adeloneivaia schubarti Barros & O. Mielke, 1970, Eacles penelope (Cramer, 1775) and Megaceresa pulchra (Bouvier, 1923) are recorded for the first time in Maranhão state and Northeast Brazil and Eacles fairchildi May & Oiticica, 1941, only for Maranhão. The record of five Ceratocampinae (Saturniidae) species increases the knowledge on the diversity and the importance of preserving those of this subfamily in the Cerrado biome of Maranhão state and the Northeast region of Brazil.
Novos registros de espécies de Ceratocampinae (Lepidoptera: Saturniidae) para o Cerrado do Maranhão, Brasil
Keywords: Conservation; Diversity; Moths; Northeast Brazil